High-performance direct ethanol fuel cell using nitrate reduction reaction. (6th September 2018) - Ma, Kyeng-Bae; Han, Sang-Beom; Kwon, Suk-Hui; Kwak, Da-Hee; Park, Kyung-Won
Abstract: In this study, we propose a high-performance direct ethanol fuel cell (DEFC) using nitrate reduction reaction with a carbon felt electrode (DEFC-HNO3 ) instead of oxygen reduction reaction (ORR) on a Pt catalyst (DEFC-O2 ). The activation energy for the nitrate reduction reaction on the carbon electrode is found to be relatively low at ∼14.2 kJ mol −1, compared to the ORR. By using the nitrate reduction reaction at the cathode and oxidation of ethanol as a fuel at the anode, the DEFC shows a significantly high open circuit voltage of 0.85 V and two-fold maximal power density of 68 mW cm −2 at 80 °C, compared to the DEFC-O2, due to the significantly fast reaction rate of the nitrate reduction reaction. Highlights: We proposed a direct ethanol fuel cell using nitrate reduction reaction (DEFC-HNO3 ). The activation energy for the nitrate reduction reaction was lower than ORR. DEFC-HNO3 showed significantly improved performance compared to DEFC-O2 . The fast nitrate reduction reaction could result in the enhanced performance of DEFC.